Sociodemographic predictors of mental health service utilization among young adults with support in daily living in Sweden: a register-based study - Jenny Meyer; Sergej Engström; Maria Löthberg; Steve Berggren; Adriana Ramirez; Sonya Girdler; Tatja Hirvikoski; Sven Bölte; Ulf Jonsson (BMC Psychiatry)
Abstract Background An increasing number of young adults in Sweden are being granted support in daily living through social services. To enhance service planning and resource allocation for this growing group of young service users, we aimed to provide an overview of the social and health-related circumstances of young adults recently granted support in daily living. We had a particular focus on mental health service utilization and whether socio-demographic factors influence the use of care. Methods Swedish nationwide register data were used to describe the sociodemographic characteristics and utilization of mental health services, including outpatient and inpatient care, treatment for suicidal behavior and pharmacological treatment. Sociodemographic predictors (sex, age, country of birth, education, and parental education) of mental health service utilization were explored using binary logistic regression. Results All young adults (ages 18–29) granted support between 2017 and 2021 (N = 15,024; 49.2% female) were included. Unfavorable social circumstances were common, including truncated education, unemployment, and the need for financial assistance. Many had a history of psychiatric inpatient care (40.0%) and treatment for suicidal behavior (15.7%). The majority received psychiatric outpatient care (71.6%) and psychopharmacological treatment (73.9%) during their granting year. Common conditions for care included attention deficit hyperactivity disorder, anxiety and fear-related disorders, mood disorders, and autism spectrum disorder. Co-occurring conditions were prevalent. Utilization of mental health services was more common among females, particularly regarding treatment for suicidal behavior (adjusted OR 2.52; 95% CI 2.16–2.93). Higher educational level and being Swedish-born were associated with a greater likelihood of utilizing outpatient care and psychopharmacological treatment. In contrast, those born in Sweden were less likely than foreign-born to be admitted to inpatient care (adjusted OR 0.66; 95% CI 0.59–0.74). Conclusions While social services recognize the support needs of this group of young adults, our findings suggest that sociodemographic characteristics such as sex, education level, and country of birth may facilitate or obstruct their access to mental health services. It is essential to coordinate efforts so that young adults with support in daily living can seek and access the mental health services they need. Clinical trial number Not applicable.